Human occupation of northern Europe in MIS 13: Happisburgh Site 1 (Norfolk, UK) and its European context. (1st May 2019) - Lewis, Simon G.; Ashton, Nick; Field, Michael H.; Hoare, Peter G.; Kamermans, Hans; Knul, Monika; Mücher, Herman J.; Parfitt, Simon A.; Roebroeks, Wil; Sier, Mark J.
Abstract: The timing, environmental setting and archaeological signatures of an early human presence in northern Europe have been longstanding themes of Palaeolithic research. In the space of 20 years, the earliest record of human occupation in Britain has been pushed back from 500 ka (Boxgrove) to 700 ka (Pakefield) and then to >800 ka (Happisburgh Site 3). Other sites also contribute to this record of human occupation; a second locality at Happisburgh, referred to as Site 1, attests to human presence at around 500 ka (MIS 13). This paper provides the first comprehensive account of research undertaken at Happisburgh Site 1 since 2000. The early human landscape and depositional environment was that of a river floodplain, where an active river channel, in which a grey sand was deposited, was abandoned, forming a floodplain lake, with marginal marsh/swamp environments, which was infilled with organic mud. This succession is sealed by Middle Pleistocene glacial deposits. An assemblage of 199 flint flakes, flake tools and cores was recovered from the grey sand and organic mud. The evidence from Happisburgh Site 1 is placed in the context of the wider British and European MIS 13 record. The growing evidence for a significant dispersal of humans into northern Europe around 500 ka raises critical questions concerning the environmental conditions under which this took place. We also consider the evolutionary and behavioural changes in human populations that might have enabled the more widespread and persistent period of human presence in northern Europe at this time. Highlights: Comprehensive account of the geology and archaeology at Happisburgh Site 1. Lower Palaeolithic assemblage comprising flakes, flake tools, cores and a handaxe. Reconstruction of local environment and landscape of human occupation. Assessment of wider context for human occupation of Europe in MIS 13.